Doomed to extinction by mining: a new species of Hoplocryptanthus (Bromeliaceae: Bromelioideae) from Congonhas, Minas Gerais, Brazil - Castro, João Luís L. M. De; Ribeiro, Otávio B. C.; Leme, Elton M. C.; Almeida, Pedro S. De; Faria, Ana Paula G. De (Phytotaxa, 2025)
A new species of Hoplocryptanthus, a member of the bromelioid “Cryptanthoid complex”, is described based on plants discovered in a ferruginous rupestrian grassland located in the southern Iron Quadrangle region, Minas Gerais state, Brazil. Hoplocryptanthus serrapiresensis is endemic to the Pires Range, a region under strong threat by mining exploitation. The morphological characters of H. serrapiresensis are discussed in comparison with H. knegtianus and H. tiradentesensis. This microendemic species is assessed as Critically Endangered (CR), reinforcing the need for a strategy to protect the biodiversity of the region. Characters related to leaves proved useful in the taxonomic delimitation of this new species. Morphological analyses also validated and reinforced the diagnostic floral and inflorescence characters used in the circumscription of Hoplocryptanthus.